Thrombin generation in patients after acute deep-vein thrombosis - ten Cate-Hoek, Arina J.; Dielis, ArneW J. H.; Spronk, Henri M. H.; van Oerle, Rene; Hamulyak, Karly; Prins, Martin H.; ten Cate, Hugo (Thrombosis and Haemostasis, 2008)
Thrombin generation measurement may be of value for assessing the risk of venous thromboembolism, but its long term profile has not been assessed in patients. We evaluated thrombin generation by Calibrated Automated Thrombogram (CAT) in plasma during follow up of 104 consecutive patients after an acute episode of deep venous thrombosis. Blood was drawn three times over the course of 24 months. Thrombin generation was measured in absence and presence of thrombomodulin and compared to a reference range derived from thrombin generation curves in 137 healthy volunteers. Thrombin generation of patients showed significantly higher endogenous thrombin potential (ETP) and peak height compared to the reference population. Differences were more pronounced in assays triggered with I pM TF. Inhibition by thrombomodulin was attenuated in patients off anticoagulants as compared to the reference population (21 % vs.42.2%, p<0.0001); inhibition in patients on anticoagulant treatment was less pronounced (9.7%, p<0.000l). Protein C activity, protein S antigen as well as free protein S showed highly negative correlation with ETP in all patients. A significant negative relation was found between FVIII levels and thrombomodulin induced reduction of ETP and peak height. In conclusion, thrombin generation by CAT reflects changes in coagulation status in patients following athromboembolic event and is most sensitive at CAT analysis triggered with I pM TEA role for factor VIII as an important attributable cause of hypercoagulability is reflected by the reduced inhibitory effect of thrombomodulin at high factor VIII levels.
Keywords: Deep vein thrombosis; factor VIII; hypercoagulability; thrombin